2017
DOI: 10.1016/j.wneu.2017.07.151
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Aquaporin-1 and Aquaporin-4 Expression in an Intramedullary Spinal Cord Ependymal Cyst: Case Report

Abstract: Background Intramedullary ependymal cysts of the spinal cord are rare, benign fluid filled cysts usually situated along the ventral surface of the spinal cord. Since they were first described, only 32 cases have been reported. Thus, owing to the rarity at which these cysts are encountered, their management and pathogenesis remain controversial. While some have previously advocated for cysto-subarachnoid shunt placement for symptomatic ependymal cysts, others have argued for complete cyst resection or simple fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 9 , 10 Only a quarter of intramedullary ependymal cysts and a few extramedullary ependymal cysts can be completely removed, 11 and total resection can worsen neurological damage. 3 , 6 , 8 , 10 , 12 Up to now, almost all literature reports have unanimously selected the posterior median spinal cord sulcus to cut into the location of the cyst ( Table 1 ). The intramedullary ependymal cyst grows slowly, and the location of the cyst is off-center and not communicating with the central canal, which causes the spinal cord to swell and push and rotate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 , 10 Only a quarter of intramedullary ependymal cysts and a few extramedullary ependymal cysts can be completely removed, 11 and total resection can worsen neurological damage. 3 , 6 , 8 , 10 , 12 Up to now, almost all literature reports have unanimously selected the posterior median spinal cord sulcus to cut into the location of the cyst ( Table 1 ). The intramedullary ependymal cyst grows slowly, and the location of the cyst is off-center and not communicating with the central canal, which causes the spinal cord to swell and push and rotate.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the pathological diagnosis of ependymal cyst. 3 Postoperative Follow-up Postoperative MRI showed that the cyst was significantly reduced, approximately 3 Â 3 Â 15 mm in size, and compression of the spinal cord was relieved. Postoperative neck pain disappeared, and medial numbness of both upper limbs was alleviated, but there was localized intermittent tingling in the right scapular region with a pain score of 4.…”
Section: Histopathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…
Cyst-subarachnoid shunting is a standard technique for the surgical treatment of spinal cord ependymal cysts. 1,2 In this video, we present a case where a modified technique of cyst-subarachnoid shunt was used. In contrast to the standard technique, 3-5 the shunt tube passes through the anterior and posterior walls of the cyst.
…”
mentioning
confidence: 99%
“…Cyst-subarachnoid shunting is a standard technique for the surgical treatment of spinal cord ependymal cysts. 1,2…”
mentioning
confidence: 99%